Quadrupolar Cyclopenta[hi]aceanthrylene‐Based Electron Donor‐Acceptor‐Donor Conjugates: Charge Transfer versus Charge Separation. (5th September 2019) - Schierl, Christoph; Alex, Wiebke; Mateo, Luis M.; Ballesteros, Beatriz; Shimizu, Daiki; Osuka, Atsuhiro; Torres, Tomas; Guldi, Dirk M.; Bottari, Giovanni
Abstract: Cyclopenta[ hi ]aceanthrylenes (CPAs) have been functionalized at two of the peripheral positions with electronically inert trimethylsilylethynyl (1 ), as well as with electron‐donating 4‐ethynyl‐ N, N ‐dimethylaniline (2 ), ethynyl Zn II phthalocyanine (3 ), and ethynyl Zn II porphyrin (4 ) units. Consistent with X‐ray crystal structures of 2 and 4, analyses of absorption and fluorescence of 2 –4 point to strong electronic communication between the CPA and the peripheral units, affording quadrupolar electron donor‐acceptor‐donor charge‐transfer conjugates. By virtue of their quadrupolar/dipolar charge‐transfer characters in the excited state, 2 –4 exhibit fluoro‐solvatochromism. Transient absorption spectroscopy confirmed delocalized quadrupolar ground states and formation of weakly solvent stabilized quadrupolar singlet excited states. The latter transform into strongly stabilized dipolar excited states before deactivating to the ground state in 2 and give rise to a fully charge separated state in 3 and 4 . Abstract : Karten auf den Tisch : Cyclopenta[ hi ]aceanthrylen (CPA), das an zwei seiner peripheren Positionen mit Trimethylsilylethinyl‐ sowie elektronendonierenden 4‐Ethinyl‐ N, N ‐dimethylanilin‐, Ethinyl‐Zn II ‐phthalocyanin‐ und Ethinyl‐Zn II ‐porphyrin‐Einheiten funktionalisiert ist, wurde hergestellt und mit photophysikalischen, elektrochemischen und spektro‐elektrochemischen Techniken untersucht.